Adubação nitrogenada, fosfatada e potássica na cultura do eucalipto (clone i144 - E. urograndis) - Gazola, Rodolfo de Niro [UNESP] (2014)
In Brazil, much of the Eucalyptus planting is in soils area of low fertility, phosphorus (P) and potassium (K) availability and organic matter (O.M.), which implies in low nutrients supply to the plant, reflecting the reduced productivity. In this context, it was aimed to evaluate nitrogen (N), P and K fertilizations on plant growth Eucalyptus aiming nutritional quality and high productivity. Experiment was conducted at Renascença Farm, agricultural fund managed by Cargill Agricola S/A located in Três Lagoas/MS. Experimental design was a randomized block with ten treatments and five replications. Treatments consisted of N rates (0, 70, 105 and 140 kg ha- 1), P rates (0, 40, 70 and 100 kg ha-1 P2O5) and K rates (0, 90, 135 and 180 kg ha-1 K2O). Nitrogen and K were applied at planting and top-dressing and P rates only at planting. It was evaluated: diameter at breast height (DBH), plant height, volume of wood with bark and leaf analysis of macronutrients concentrations. The DBH and volume were influenced positively by N fertilization, P and K, since the eucalyptus growth in DAP, height and volume increased with P and K fertilization. The macronutrients concentrations were appropriate even in the absence of N, P and K application. Increasing rates of K was increased foliar concentrations of K and decreased calcium (Ca) and magnesium (Mg)